THE EFFECT OF ENVIRONMENTAL SANITATION ON STUNTING CASES AMONG TODDLERS IN SOUTHEAST SULAWESI IN 2022: A LITERATURE REVIEW - Yulisti, Sry; Tosepu, Ramadhan; Saptaputra, Syawal Kamiluddin (Universitas Halu Oleo, 2024)
ABSTRACT Stunting is the term for linear growth disorders (length/height based on age) in the early years of life. In 2022, stunting in Indonesia was around 21.6%, tending to still be above 20% (WHO standards). The environment is one of the factors causing stunting, including the home environment, such as the house's physical condition, sanitary condition, and sanitation facilities. Poor environmental conditions are related to water, sanitation, and hygiene. This research used a literature study method through health articles related to the effect of environmental sanitation on stunting cases in Southeast Sulawesi from the publication years 2018 to 2022. The selected articles were the articles that used qualitative and quantitative research. The results obtained from several studies showed a relationship between the use of drinking water quality and the incidence of stunting, stating that toddlers with poor drinking water quality would experience stunting more often, with research results of 61.5%, the relationship between the incidence of diarrhea due to the environment (27.7%), the effect of sanitation among mothers of toddlers (100%), and knowledge related to hygiene (37.1%) on the incidence of stunting. Based on the results, six research articles were extracted regarding the relationship between the effect of environmental sanitation and the incidence of stunting among toddlers in Southeast Sulawesi, including the quality of drinking water, the incidence of diarrhea, sanitation, and knowledge related to hygiene among mothers of toddlers. Therefore, researchers hope that there will be further research based on the results of research that aims to perfect existing research, using different research approaches. Keywords: Sanitation, Environment, Stunting Toddlers, Southeast Sulawesi